The Role of Integrated Marketing Communications in Enhancement of SMEs Growth in South Africa - LEKHANYA, Lawrence Mpele (Journal of Economics and Behavioral Studies, 2015)
The intention of this paper is to discover and empirically test the knowledge gap exist with regard to the role that integrated marketing communication (IMC) plays in the enhancement of SMEs growth. A quantitative approach is followed in this paper, with a questionnaire as the research instrument and questionnaire items established through a literature review. A sample of 374 SMEs owners/managers agreed to complete the questionnaire. In order to give a descriptive overview of variables relevant to the objectives of the study, a Cronbach test was performed. Certain ability in marketing communication by SMEs was evident from the sample. However, very few marketing communication tools are fully applied in order to enhance SMEs growth. A significant starting point, in attaching importance to the role of IMC enhancement of SMEs growth, is constituted by this paper’s sample, even though it is restrictively small. Practitioners may, from this paper, understand where intervention guidelines are needed, in order to improve an IMC plan needed for SMEs. Compared to previous research done on large company practices, this paper represents an original trial to empirically apply the marketing communication approach within SMEs.